Applying the Debt Sustainability Framework for Low-Income Countries Post Debt Relief. (Policy Papers; Policy Paper, 2006)
In April 2006, the Executive Boards of the Bank and the Fund reviewed the debt sustainability framework (DSF) for low-income countries and the implications of the multilateral debt relief initiative. Directors thought that the DSF was broadly appropriate and that no major changes were warranted, but saw scope for additional guidance on the application of the framework in a context where the apparent borrowing space created by debt relief raises new challenges in terms of policy advice. Most Directors supported a case-by-case approach for assessing the appropriate pace of debt accumulation in countries with debt below the DSF thresholds, but requested the development of specific recommendations on the implementation of such a case-by-case approach.